Factors Influencing Women’s Career Choice in STEM: A Case Study of Batam State Polytechnic Alumni - Shinta Wahyu Hati; Yesica Rumata Nababan (Interdisciplinary Social Studies, 2026)
This study aims to determine the factors influencing women's career choices and the most dominant factor among female alumni from the Department of Mechanical and Electrical Engineering at Batam State Polytechnic, particularly in the field of STEM (Science, Technology, Engineering, and Mathematics) engineering. This study uses a quantitative approach with the factor analysis method and a sample of 100 respondent alumni selected via the saturated sampling technique. The results showed that the most dominant factor in women's career choices in STEM engineering is the personality factor. This study confirms that, although personality emerged as the dominant factor, the financial reward factor and family environment factor also influence women's career decisions. In this study, 11 variables were reduced to three key factors driving women's career choices in engineering: personality, financial rewards, and family environment. The practical implication of this study is the need for mentorship programs, increased information about the prospects of financial rewards, and more intensive family support to encourage more women to pursue careers in engineering. This research makes a theoretical contribution to understanding women's career motivations in STEM fields and can serve as a basis for promotion to prospective students.